Exposing the old theories of IOK to new candidates : an analytical reflection on IIUM philosophy of knowledge - Ahmed Shogar, Ibrahim Adam (http://iium.edu.my, 2013)
International Islamic University Malaysia (IIUM) is distinguished from other institutions of higher learning by its philosophy of knowledge which derived from Islamic worldview. Science grows and flourishes only within a certain epistemological paradigm which provides the philosophy and framework for knowledge production and propagation. The worldview explains the overall perspective of the world that enables scientists to establish their basic assumptions and answer their ultimate questions. Based on these principals, IIUM has been playing a crucial role, over the last three decades, in producing the interdisciplinary scholars who imbued with knowledge and moral values. Adopting the analytical research method, the paper has explored the theoretical and practical implications of IIUM philosophy of knowledge and its role in the process of knowledge production and propagation.